"De Colorando Auro" medieval colour surface treatment of silver gilded statuettes decorating the Holy Lady Shrine of Huy (13th century, Belgium). Issue 3 (5th January 2015) - Crabbé, Amandine C.; Ceglia, Andrea; Cerezo, Jose; Wouters, Helena J. M.; Mocuta, Cristian; Terryn, Herman; Vandendael, Isabelle
Abstract : Medieval chemical coloration revealed by XANES measurements on the silver gilded statuettes from the Holy Lady Shrine, 13 th century. It is from the Holy Lady collegiate church in Huy, Belgium. Abstract : In previous papers, we showed that it is possible to modify the colour of gilding on the silver substrate by applying a surface chemical treatment after it has been burnished [Crabbé et al., Surf. Interface Anal. 2008, 40, 467; Crabbé et al. Applied Physics A, 2013, 111, 39]. These types of techniques are recounted in many medieval and older manuscripts [Crabbé et al., Arch. des Biblio. de Belgique. 2011, 94, 1581]. They have to be taken into account when applying conservation–restoration cleaning to silver gilded statuettes such as the ones from the Holy Lady Shrine from Huy (13 th century, Belgium) [Didier et al., Bull. de L'IRPA 1970, 12, 5]. Scanning Electron Microscopy coupled with Energy Dispersive X-ray spectroscopy (SEM-EDX) and synchrotron X-ray Absorption Spectroscopy (XAS) were carried out both on model and historical samples with the aim of determining if medieval colour treatment has been applied in an efficient way to the silver gilded statuettes of the shrine. Those results are of first importance to the conservator-restorer responsible for the shrine restoration treatment. They will influence the treatment applied to the shrine but also the interpretation of the art-piece, its final aspect and the art-history of medieval times.